Comparative Analysis of Business Orientation, Efficiency, Financial Stability and Asset Quality in Conventional BPR and Sharia BPR - Najmudin, Najmudin; Nurbaeti, Anindya Rizki; Shaferi, Intan (Indonesian Journal of Islamic Business and Economics (IJIBE), 2024)
This paper aims to investigate the difference by comparing the financial performances of conventional and Sharia banks located in Banyumas Regency and listed in the FSA (Financial Services Authority). The technique to select the population is purposive sampling. The proxies of the financial performances include orientation of business, efficiency level, stability of finance, and quality of asset. This paper find that all four variables are significantly different in the average between conventional and Sharia rural banks.